Palladium-Catalyzed Dearomative Cyclocarbonylation by CN Bond Activation - Yu, Hui; Zhang, Guoying; Huang, Hanmin (Angewandte Chemie International Edition, 2015)
A fundamentally novel approach to bioactive quinolizinones is based on the palladium‐catalyzed intramolecular cyclocarbonylation of allylamines. [Pd(Xantphos)I2], which features a very large bite angle, has been found to facilitate the rapid carbonylation of azaarene‐substituted allylamines into bioactive quinolizinones in good to excellent yields. This transformation represents the first dearomative carbonylation and is proposed to proceed by palladium‐catalyzed CN bond activation, dearomatization, CO insertion, and a Heck reaction. Dearomatization: A highly efficient dearomative cyclocarbonylation reaction proceeds by palladium‐catalyzed CN bond activation, dearomatization, CO insertion, and a Heck reaction. This transformation represents the first general catalytic method for the synthesis of valuable bioactive quinolizinones.